Avaliação das manifestações clínicas e microscópicas dos linfomas em glândulas salivares maiores - Gabriela Ribeiro de Araújo (2024)
Non-Hodgkin's lymphomas account for 2.8% of all new cancer cases worldwide and are the third most common group of malignant neoplasms in the head and neck region. The major salivary glands represent the third most common extranodal site affected by lymphoma in the head and neck region; however, in the major salivary glands it is very rare, representing approximately 1.7-3.1% of all salivary gland neoplasms, affecting most cases in the parotid glands (79%), followed by the submandibular glands (18%) and sublingual glands (1%). The most common subtypes are mucosa- associated lymphoid tissue lymphoma (MALT), follicular lymphoma (FL) and diffuse large B-cell lymphoma (DLBCL), and the frequency of these neoplasms is associated with the simultaneous occurrence of systemic conditions that predispose to the development of lymphoid neoplasms such as Sjögren's Syndrome(SS). However, the literature on lymphomas in major glands remains very scarce and prevents us from properly understanding the characteristics of these patients. Therefore, the aim of this study was to evaluate the clinical and microscopic manifestations of lymphomas in the major salivary glands. To this end, all cases diagnosed as lymphomas affecting these anatomical sites were retrospectively retrieved from the pathology archives of a number of institutions. Clinical data was collected on gender, age, location, clinical presentation, time of evolution, status, staging and occurrence of SS, and histopathological information was collected from paraffin blocks and slides in hematoxylin and eosin and accessible immunohistochemistry. The results obtained were evaluated descriptively. The series comprised 7 cases of lymphomas in the sublingual gland, 16 cases in the submandibular gland and 12 cases in the parotid gland. Clinically, the lymphomas presented as asymptomatic enlargement, with the most frequent subtypes being low-grade mature B-cells (MALT, FL, MCL), but high- grade subtypes were also observed (LDGCB, SOE). Two patients, one with mantle cell lymphoma (MCL) and the other with LDGCB,SOE in the sublingual gland presented with disseminated disease, and only three cases of MALT lymphoma in the parotid gland presented with SS. Treatment depended on the microscopic subtype and stage of the tumor, ranging from surgery to chemotherapy regimens with R-CHOP and radiotherapy. Prognosis was mainly favorable for low-grade cases (MALT,FL), and only two sublingual patients (LDGCB,SOE, MCL) and three submandibular patients (LDGCB,SOE, plasmablastic lymphoma and MALT) died after diagnosis. In this study we conclude that lymphomas in the major salivary glands are mainly affected by low- grade mature B-cell neoplasms (MALT, FL, MCL) and these patients should undergo a careful systemic evaluation to determine whether the disease is a primary or disseminated neoplasm.